(x+1)(x+3)=9

Simple and best practice solution for (x+1)(x+3)=9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x+1)(x+3)=9 equation:


Simplifying
(x + 1)(x + 3) = 9

Reorder the terms:
(1 + x)(x + 3) = 9

Reorder the terms:
(1 + x)(3 + x) = 9

Multiply (1 + x) * (3 + x)
(1(3 + x) + x(3 + x)) = 9
((3 * 1 + x * 1) + x(3 + x)) = 9
((3 + 1x) + x(3 + x)) = 9
(3 + 1x + (3 * x + x * x)) = 9
(3 + 1x + (3x + x2)) = 9

Combine like terms: 1x + 3x = 4x
(3 + 4x + x2) = 9

Solving
3 + 4x + x2 = 9

Solving for variable 'x'.

Reorder the terms:
3 + -9 + 4x + x2 = 9 + -9

Combine like terms: 3 + -9 = -6
-6 + 4x + x2 = 9 + -9

Combine like terms: 9 + -9 = 0
-6 + 4x + x2 = 0

Begin completing the square.

Move the constant term to the right:

Add '6' to each side of the equation.
-6 + 4x + 6 + x2 = 0 + 6

Reorder the terms:
-6 + 6 + 4x + x2 = 0 + 6

Combine like terms: -6 + 6 = 0
0 + 4x + x2 = 0 + 6
4x + x2 = 0 + 6

Combine like terms: 0 + 6 = 6
4x + x2 = 6

The x term is 4x.  Take half its coefficient (2).
Square it (4) and add it to both sides.

Add '4' to each side of the equation.
4x + 4 + x2 = 6 + 4

Reorder the terms:
4 + 4x + x2 = 6 + 4

Combine like terms: 6 + 4 = 10
4 + 4x + x2 = 10

Factor a perfect square on the left side:
(x + 2)(x + 2) = 10

Calculate the square root of the right side: 3.16227766

Break this problem into two subproblems by setting 
(x + 2) equal to 3.16227766 and -3.16227766.

Subproblem 1

x + 2 = 3.16227766 Simplifying x + 2 = 3.16227766 Reorder the terms: 2 + x = 3.16227766 Solving 2 + x = 3.16227766 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + x = 3.16227766 + -2 Combine like terms: 2 + -2 = 0 0 + x = 3.16227766 + -2 x = 3.16227766 + -2 Combine like terms: 3.16227766 + -2 = 1.16227766 x = 1.16227766 Simplifying x = 1.16227766

Subproblem 2

x + 2 = -3.16227766 Simplifying x + 2 = -3.16227766 Reorder the terms: 2 + x = -3.16227766 Solving 2 + x = -3.16227766 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + x = -3.16227766 + -2 Combine like terms: 2 + -2 = 0 0 + x = -3.16227766 + -2 x = -3.16227766 + -2 Combine like terms: -3.16227766 + -2 = -5.16227766 x = -5.16227766 Simplifying x = -5.16227766

Solution

The solution to the problem is based on the solutions from the subproblems. x = {1.16227766, -5.16227766}

See similar equations:

| 2x^2-72=8x+45 | | 2u^2=5u+3 | | 9x^2+12x+4=24 | | (x+7)(x-5)=13 | | 5p^2+28p+15=0 | | 165-5x=22x+15 | | -8z-3z=24-3 | | 14+-8x=59+-29x | | 4m+6m=66 | | 14-8x=59-29x | | 3x+7=13-7x | | 112-2x=4x+22 | | 4x(2x-1)+2(2x-1)(2x-1)=0 | | 2-5x=14+9x | | -25=5(x-7)+5x | | 28=-6x+4(x+5) | | 28=-6x+4(x-5) | | 28=-6x+4(u-5) | | -18=-3x+6(x-7) | | 34=8(x+5)-5x | | 4x(2x-1)+2(4x+1)=0 | | 2x^2-11=8x+8 | | 300-20x+x^2=0 | | 3(x-1)-5=4x-7 | | 7x-3y+2z=0 | | (2x)*(3x-5)= | | 5x+26(x-2)=227 | | x^2+5x-60=0 | | 9-2(x+2)=8+x | | 36(x-1)-4(x-5)=9(x+5) | | 2x/7-3x/5=6/35 | | -2x^2+4x+6=0 |

Equations solver categories